2021
DOI: 10.1007/s12032-021-01526-6
|View full text |Cite
|
Sign up to set email alerts
|

Melittin inhibits the expression of key genes involved in tumor microenvironment formation by suppressing HIF-1α signaling in breast cancer cells

Abstract: Purpose: HIF-1α has critical roles in formation of Tumor microenvironment by regulating genes involved in angiogenesis and anaerobic respiration. TME fuels tumors growth and metastasis and presents therapy with several challenges. Therefore, we aimed to investigate if Melittin disrupts HIF-1α signaling pathway in breast adenocarcinoma cell line MDA-MB-231.Methods: breast adenocarcinoma cell line MDA-MB-231 was cultured in presence of different doses of Melittin and MTT assay was carried out to measure Melittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Furthermore, the use of melittin in these same strains has already been shown to inhibit the epithelial-mesenchymal transition of tumor cells 45 , corroborating the findings of Jeong et al 36 . Experiments using cervical carcinoma and mammary carcinoma cell lines also showed a relationship between the suppressive action of melittin on the expression of VEGF and HIF-1α 46,47 and its inhibitory effect on migration and invasion of tumor cells, confirming the findings of Zhang and Chen 34 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, the use of melittin in these same strains has already been shown to inhibit the epithelial-mesenchymal transition of tumor cells 45 , corroborating the findings of Jeong et al 36 . Experiments using cervical carcinoma and mammary carcinoma cell lines also showed a relationship between the suppressive action of melittin on the expression of VEGF and HIF-1α 46,47 and its inhibitory effect on migration and invasion of tumor cells, confirming the findings of Zhang and Chen 34 .…”
Section: Discussionsupporting
confidence: 72%
“…It is formed by 26 amino acids 10 and is the main active component of apitoxin 19 . Recent preclinical studies (in vitro, in vivo and in silico) have conducted experiments and demonstrated the anticancer effects of melittin through different mechanisms of action in cell cultures of osteosarcoma 20, gastric carcinoma 21,22 , mammary carcinoma 23,24,25 , urothelial carcinoma 26 and melanoma 27 . Its high non-selective cytotoxic activity makes it a promising natural molecule for the development of new technologies and drugs for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…MEL also showed the potential to promote mitofusin-1 (Mfn1) and dynamin-related protein 1 (Drp1) expression and apoptosis in 4T1 cells ( Moghaddam et al, 2020 ). After 5% O 2 induction in MDA-MB-231 cells, the hypoxia-inducible factor-1α (HIF-1α) signaling pathway was inhibited by MEL and the expression of NF-κB, HIF-1α, vascular endothelial growth factor A (VEGFA) and lactate dehydrogenase A (LDHA) decreased, while the expression of Bax and tumor necrosis factor-α (TNF-α) was reversed, ultimately disrupting the tumor microenvironment (TME) of cancer cells and activating the phenomenon of apoptosis ( Mir Hassani et al, 2021 ).…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…Melittin (MEL), a polypeptide and the capital ingredient of honey bee venom, declined HIF-1α/VEGF levels via the suppression of ERK and mTOR/p70S6K signaling ( Shin et al, 2013 ). It downregulated NF-κB to inhibit the HIF-1α/VEGFA and LDHA expression that caused angiogenesis and descent pH via anaerobic metabolism, in TME, respectively ( Mir Hassani et al, 2021 ). CDDO-Me (Bardoxolone methyl), an analog of the natural triterpenoids oleanolic acid, the methyl-ester of the 2-cyano-3,12-dioxooleana-1,9 (11)-dien-28-oic acid (CDDO), have been abundantly advised for pharmacological applications, including tumor interference ( Borella et al, 2019 ).…”
Section: Co-regulating Tumor Angiogenesis and Tme By Tcmmentioning
confidence: 99%